Association between Inflammatory Bowel Disease and Pancreatitis: A PRISMA-Compliant Systematic Review. (3rd August 2020) - Li, Pengfan; Chen, Kanjun; Mao, Zheng; Luo, Yue; Xue, Yan; Zhang, Yuli; Wang, Xueying; Zhang, Lihang; Gu, Sizhen; Dou, Danbo
Abstract : Background/Objectives . This systematic review was conducted to investigate the association between pancreatitis and IBD. Methods . MEDLINE, Embase, and CENTRAL were systematically searched for correlative studies till 2 November 2019. RevMan5.3 was used to estimate relevance. Results . Three studies with 166008 participants were included. The risk of pancreatitis significantly increased in the patients with CD (OR, 3.40; 95% CI, 2.70-4.28; P < 0.00001 ) and UC (OR, 2.49; 95% CI, 1.91-3.26; P < 0.00001 ). Increased risks of CD (OR, 12.90; 95% CI, 5.15-32.50; P < 0.00001 ) and UC (OR, 2.80; 95% CI, 1.00-7.86; P = 0.05 ) were found in patients with chronic pancreatitis. As for patients with acute pancreatitis, there were significant association of CD (OR, 3.70; 95% CI, 1.90-7.60; P = 0.0002 ), but were not UC. Conclusions . The evidence confirmed an association between pancreatitis and IBD. When pancreatitis patients have chronic diarrhea and mucus blood stool or IBD patients have repeated abdominal pain and weight loss, they should consult pancreatic and gastrointestinal specialists.